2005
DOI: 10.1381/0960892054621071
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-prandial Plasma Ghrelin Levels Do Not Correlate with Satiety or Failure to Achieve a Successful Outcome after Roux-en-Y Gastric Bypass

Abstract: Failure to lose weight after RYGBP does not correlate with pre- or post-prandial ghrelin plasma levels. Ghrelin levels were inversely proportional to BMI and did not correlate with satiety. These data do not support a role for higher plasma ghrelin levels for inadequate weight loss after RYGBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The majority of authors agree upon the fact that ghrelin is an important determinant of energy homeostasis, a peripherally secreted orexigenic hormone acting in key central pathways, with measurable levels demonstrating meal-to-meal variation. Noteworthy, to our knowledge, no study to date has demonstrated that ghrelin levels postoperatively are predictors of success in patients after LRYGB [36].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The majority of authors agree upon the fact that ghrelin is an important determinant of energy homeostasis, a peripherally secreted orexigenic hormone acting in key central pathways, with measurable levels demonstrating meal-to-meal variation. Noteworthy, to our knowledge, no study to date has demonstrated that ghrelin levels postoperatively are predictors of success in patients after LRYGB [36].…”
Section: Discussionmentioning
confidence: 95%
“…Because ghrelin levels have been shown to be low after LRYGB in some studies [20,30,[31][32][33][34][35][36], it has been proposed that lower ghrelin levels may contribute to the success of some surgical weight loss procedures, including LRYGB [14,15,20] and possibly laparoscopic adjustable gastric banding [30]. However, data have been inconsistent [10,12,15,16,25,37].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with optimal restriction experienced greater satiety, but there was no difference in ghrelin levels between the two groups. In RYGB patients, Christou and coworkers 121 looked at fasting plasma ghrelin in those who achieved successful weight loss (EWL 72%) and less than ideal weight loss (EWL 27%) 3 years after surgery. There was no difference between fasting or postprandial levels in the two groups and no correlation between ghrelin levels and their visual analog scale score.…”
Section: Ghrelinmentioning
confidence: 99%
“…Ghrelin levels are increased with diet induced weight loss. Interestingly RYGBP has been shown to be associated with low levels of circulating ghrelin that persist at 1 and 3 years followup [42,43] . On the contrary, LASGB, VBG [44] , and antireflux surgical procedures [37,[45][46][47][48] are not associated with a decline of the circulating levels of ghrelin [42] .…”
Section: Physiology Of Lsgmentioning
confidence: 99%